تفويض السلطة وعلاقته بالأداء الوظيفي : دراسة ميدانية على الإداريين بمدارس التعليم الأساسي ببلدية زليتن (Journal of Academic Research, 2025)
This research aims to identify the degree of delegation of authority and its relationship to job performance from the viewpoint of administrators in Zliten Municipality. To achieve this, the descriptive analytical method was used. The study population comprised all administrators in basic education schools in Zliten Municipality. A random sample of (104) male and female administrators was drawn. A questionnaire was adopted as the data collection tool, consisting of (49) items distributed across two axes: the delegation of authority axis (27 items) and the job performance axis (22 items). Data were processed using the Statistical Package for the Social Sciences (SPSS).The research reached several key findings, including:The degree of delegation of authority among principals in basic education schools in Zliten Municipality was high, with an arithmetic mean of (3.80) and a percentage of 70.04%.The level of job performance among administrators in basic education schools in Zliten Municipality was also high, with an arithmetic mean of (4.02) and a percentage of 75.02%.There is a direct positive relationship between the delegation of authority and job performance; as the level of delegation of authority increased, job performance also increased by 41.01%.The results also showed no statistically significant differences in the opinions of administrators regarding the level of delegation of authority and the level of job performance attributable to the variables of (gender, academic qualification, and years of experience).The majority of the sample members were female, representing 78.08%, and held university qualifications.